Exploring the impact of learning objects in middle school mathematics and science classrooms: A formative analysis - Robin H. Kay; Liesel Knaack (The Canadian Network for Innovation in Education (CNIE), 2008)
The current study offers a formative analysis of the impact of learning objects in middle school mathematics and science classrooms. Five reliable and valid measure of effectiveness were used to examine the impact of learning objects from the perspective of 262 students and 8 teachers (14 classrooms) in science or mathematics. The results indicate that teachers typically spend 1-2 hours finding and preparing for learning-object based lesson plans that focus on the review of previous concepts. Both teachers and students are positive about the learning benefits, quality, and engagement value of learning objects, although teachers are more positive than students. Student performance increased significantly, over 40%, when learning objects were used in conjunction with a variety of teaching strategies. It is reasonable to conclude that learning objects have potential as a teaching tool in a middle school environment. L'impacte des objets d'apprentissage dans les classes de mathématique et de sciences à l'école intermédiaire : une analyse formative Résumé : Cette étude présente une analyse formative de l'impacte des objets d'apprentissage dans les classes de mathématique et de sciences à l'école intermédiaire. Cinq mesures de rendement fiables et valides ont été exploitées pour examiner l'effet des objets d'apprentissage selon 262 élèves et 8 enseignants (414 classes) en science ou mathématiques. Les résultats indiquent que les enseignants passent typiquement 1-2 heures pour trouver des objets d'apprentissage et préparer les leçons associées qui seraient centrées sur la revue de concepts déjà vus en classe. Quoique les enseignants aient répondu de façon plus positive que les élèves, les deux groupes ont répondu positivement quant aux avantages au niveau de l'apprentissage, à la qualité ainsi qu'à la valeur motivationnelle des objets d'apprentissage. Le rendement des élèves aurait aussi augmenté de façon significative, plus de 40%, quand les objets d'apprentissage ont été exploités avec une variété de stratégies d'enseignement. Il serait donc raisonnable de conclure que les objets d'apprentissage ont un potentiel comme outils d'enseignement à l'école intermédiaire.